Multimodal Metadiscourse: A Model Development and Application to Spoken Political Discourse - Khalifa, Reham Mohamed El-Said (جامعة قناة السويس - كلية الآداب والعلوم الإنسانية, 2023)
تلعب عناصر الخطاب فوق الخطاب دورا حيويا في التواصل الفعال من خلال مساعدة الأخرين على فهم وتقييم والاستجابة للمعلومات التي ينقلها الكاتب أو المتحدث. لا إنها ليست مقتصرة على التعبيرات اللغوية فقط؛ بل يمكن أن تشمل مجموعة متنوعة من صيغ التواصل المختلفة. ومع ذلك، كانت الأبحاث السابقة تركز بشكل أساسي على الجانب اللغوي منها، مما يفتقر إلى إطار شامل لتحليل الخطاب فوق الخطاب بشكل دقيق في سياق متعدد الأنماط. لذلك، هدفت الدراسة الحالية إلى تحديد نموذج مناسب الدراسة جوانب الخطاب فوق الخطاب في الخطابات الشفهية، وبشكل خاص في السياقات السياسية، من منظور متعدد الصيغ (الأنماط). من أجل بناء هذا النموذج، تم استعراض الأدبيات السابقة لجمع سمات الخطاب فوق الخطاب المناسبة للخطاب الشفهي. تم دمج هذه السمات في نموذج شامل وتم التحقق من مدي مناسباتها من خلال تقييم الخبراء وتطبيقها على مثالين من الخطابات السياسية الشفهية. المثال الأول تمثل في خطاب سياسي باللغة الإنجليزية للرئيس الأمريكي السابق دونالد ترامب خلال حملته الانتخابية التمهيدية لانتخابات الولايات المتحدة 2024، والمثال الثاني تمثل في خطاب سياسي باللغة العربية للرئيس المصري عبد الفتاح السيسي في القمة الدولية للحكومات والتي انعقدت في الإمارات العربية المتحدة في يناير 2023. وأظهرت النتائج أن النموذج المقترح قابل للتطبيق على الخطب السياسية الشفهية وقد ساهم في توضيح خصائص الخطاب فوق الخطاب التي تم استخدامها من قبل الرئيسين في خطاباتهما السياسية. Metadiscourse plays a pivotal role in effective communication by aiding others in understanding, assessing, and responding to the information conveyed by a writer or speaker in the intended manner. It is not confined solely to linguistic expressions; rather, it can encompass a combination of various modes within multimodal contexts. Nevertheless, prior research has predominantly focused on linguistic metadiscourse, lacking a comprehensive framework for a thorough analysis of metadiscourse in a multimodal context. Hence, the current research aimed to identify an appropriate model for scrutinizing spoken discourses, particularly in political contexts, from a multimodal perspective. To construct this model, existing literature was reviewed to compile metadiscourse characteristics suitable for spoken discourses. These characteristics were integrated into a comprehensive model and validated through expert assessment of and application to two instances of spoken political discourse. The first example was an English political speech delivered by Donald Trump during his preliminary campaign for the 2024 USA elections. The second was an Arabic political speech by the Egyptian President Abdel-Fattah Alsisi at the International Government Summit in the UAE. The findings demonstrated that the suggested model is applicable to spoken political discourse, effectively uncovering the metadiscourse features employed by these two politicians in their speeches.
Keywords: الخطابات السياسية -- المصطلحات اللغوية -- النصوص المكتوبة -- اللغة الإنجليزية